Analysis of CO2 Emission Reduction Effect of On-Site Production Precast Concrete Member according to Factory Production Environment - Youngju Na; Bumjin Han; Seunghyun Son (Advances in Civil Engineering)
Precast concrete (PC) method of construction is preferred for excellence in the reduction of construction period, lightweight, and durability and for PC member to be mostly transported to a site after its production in the in-plant production because the in situ production of the PC member is negatively perceived because of the limitation of space or production process being complex and difficult. However, if the PC member is produced on site and installed, it is possible to reduce the carbon dioxide emissions that are generated during shipping and loading and unloading, which are indirectly required for in-plant production. Carbon dioxide emission reduction effect due to the difference between the in situ production and in-plant production process of the PC member was confirmed by the existing studies, but the study of the carbon dioxide reduction effect according to various production environments of the in-plant production has not been performed. Therefore, the purpose of this study is to analyze the CO2 emission reduction effect of the PC member produced in site according to the in-plant production environment. As a result, it was found that when PC members were produced on site, there was an effect of reducing CO2 emissions by an average of 25.64% compared to factory production. In future, the results of this study will be used as basic data for establishing a CO2 emission reduction plan at construction sites.